2018
DOI: 10.1161/jaha.118.009746
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Predictors of 30‐Day Readmission in Patients With Syncope/Collapse: A Nationwide Cohort Study

Abstract: BackgroundSyncope accounts for 0.6% to 1.5% of hospitalizations in the United States. We sought to determine the causes and predictors of 30‐day readmission in patients with syncope.Methods and ResultsWe identified 323 250 encounters with a primary diagnosis of syncope/collapse in the 2013–2014 Nationwide Readmissions Database. We excluded patients younger than 18 years, those discharged in December, those who died during hospitalization, hospital transfers, and those whose length of stay was missing. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…In our study, 5.4% of patients were readmitted for syncope within the 2‐year period. This is less than the rate of 9.3% demonstrated in a similar retrospective, cohort study on the outcomes of patients with syncope 18 . In our study, 9.6% of patients died within the study period; however, notably all deaths occurred for reasons unrelated to the syncopal event.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In our study, 5.4% of patients were readmitted for syncope within the 2‐year period. This is less than the rate of 9.3% demonstrated in a similar retrospective, cohort study on the outcomes of patients with syncope 18 . In our study, 9.6% of patients died within the study period; however, notably all deaths occurred for reasons unrelated to the syncopal event.…”
Section: Discussioncontrasting
confidence: 76%
“…This is less than the rate of 9.3% demonstrated in a similar retrospective, cohort study on the outcomes of patients with syncope. 18 In our study, 9.6% of patients died within the study period; however, notably all deaths occurred for reasons unrelated to the syncopal event. A comparable observational study found the all-cause mortality rate of patients presenting to the ED for syncope to be 7.6% at 12 months, 19 which is slightly below the findings of this study.…”
Section: Number Of Investigationsmentioning
confidence: 47%
“…We found that COPD was independently associated with increased mortality risk in patients hospitalized with syncope in this cohort; this risk was similar to patients with HF. Recently COPD has been shown to predict increased risk of hospitalization for syncope, however, mortality outcomes were not reported 23 . Potential mechanisms of syncope in COPD include cough syncope, orthostatic hypotension because of medications used for associated comorbidities, presence of pulmonary hypertension and secondary adrenal insufficiency because of corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches consume hospital resources and often lead to prolonged and unnecessary hospital length of stay (LoS) [ 1 , 3 , 4 , 5 , 6 ]. Long initial hospital stays (>3 days) are associated with greater expense, higher readmission rates within 30 days and resource utilization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%